The association between physical activity and the risk of symptomatic Barrett's oesophagus: a UK prospective cohort study. Issue 1 (January 2018) - Lam, Stephen; Alexandre, Leo; Luben, Robert; Hart, Andrew R.
Abstract : Background: Physical activity affects the functioning of the gastrointestinal system through both local and systemic effects and may play an important role in the aetiology of gastroesophageal reflux disease, Barrett's oesophagus and oesophageal adenocarcinoma. We investigated, for the first time in a large prospective cohort study, associations between recreational and occupational levels of physical activity and the incidence of Barrett's oesophagus. Participants and methods: The European Prospective Investigation of Cancer-Norfolk recruited 30 445 men and women between 1993 and 1997. Occupational and recreational levels of physical activity were measured using a baseline questionnaire. The cohort was followed up until 2015 to identify symptomatic cases of Barrett's oesophagus. Cox proportional hazard regression estimated hazard ratios (HR) for physical activity and the development of disease. Results: Two hundred and three participants developed Barrett's oesophagus (mean age: 70.6 years) the majority of whom were men (70.9%). There was an inverse association between standing occupations and disease risk [HR: 0.50, 95% confidence interval (CI): 0.31–0.82, P =0.006] when compared with sedentary jobs. Heavy manual occupations were positively associated with disease risk (HR: 1.66, 95% CI: 0.91–3.00), but conventional statistical significance was not reached ( P =0.09). No associations were found between recreational activity and the risk of Barrett's oesophagus (HR: 1.34, 95% CI: 0.72–2.50, P =0.35, highest vs. lowest levels of activity). Conclusion: Our study suggests that occupational levels of physical activity may be associated with the risk Barrett's oesophagus. However, further work is required to confirm and describe specific occupations that may be protective. Abstract : Supplemental Digital Content is available in the text.